OPTIMASI DESAIN MOLD COVER TOWING FRONT BUMPER MELALUI SIMULASI MOLDFLOW UNTUK MENGURANGI CACAT PRODUK - Abdul Wahid Arohman; Andi Muhammad Hanif Tjoppo; Edwin Sahrial Solih; Sanurya Putri Purbaningrum; Desy Agustin; Fredy Sumasto (Scientific Journal of Mechanical Engineering Kinematika, 2025)
Plastic injection molding is a method of forming a product that uses plastic (Polymer) as the main material. The resulting product must have as few defects as possible because it will reduce the quality value and customer satisfaction. In this study, the mold was made for the Front towing bumper cover product with the design and simulation stages. The simulation process uses Moldflow Software to identify possible product defects that occur with variations in melt temperature of 200, 240, and 280 (°C). The result obtained in this simulation is the optimal melt temperature for producing products in the injection molding process by selecting a temperature of 240°C. This temperature is the most optimal because it has faster fill time and cooling time, with an optimum percentage of 25% compared to the temperatures of 200 and 280 (°C). In potential defects such as air traps, weldlines, and shinkmarks, a temperature of 240 (°C) has fewer potential defects than 200 and 280 (°C).